Modelling (Social) Intra/Entrepreneurship Process - João M. S. Carvalho (Emerging Science Journal, 2022)
This study had three objectives: to discover the main concepts and theories used in research around entrepreneurship; systematize the entrepreneurial process in a model that allows teaching it more efficiently, and substantiate the model by applying it to various social entrepreneurship projects. To this end, a systematic scoping review was carried out to identify the main concepts, theories, and processes, which constitute the six crucial building blocks to someone could be successful as a(n) (social) intra/entrepreneur. Then, a design-science approach led us to use real social innovation and social entrepreneurship cases to evaluate the constructs and the model. Consequently, it is concluded that all concepts, theories and models identified can be classified as external factors (Context and Resources), internal factors (Objectives and entrepreneurial Will) and achievements (Action and Impact). The CROWAI model fits well with the data obtained on 465 innovation and social entrepreneurship projects. Thus, this model presents a more comprehensive approach, applicable to all profitable or social intra/entrepreneurship situations, allowing this new conceptual arrangement to be more easily taught. Additionally, it makes sense to use the term ‘social’ in innovation and intra/entrepreneurship because it has excellent defining power of the scope one wants to achieve with human endeavours. Doi: 10.28991/ESJ-2022-06-01-02 Full Text: PDF